Overaggressive stent expansion without intravascular imaging: impact on restenosis. Issue 1 (27th February 2014) - Chacko, Yohan; Chan, Richard; Haladyn, J Kimberly; Lim, Richard
Abstract : Objective: Aggressive stent expansion is required for optimal strut apposition, but risk of stent deformation, fracture and subsequent restenosis is potentially greater when performed without intravascular imaging guidance. We investigated how frequently stents are 'overexpanded' and whether this correlates with restenosis. Design and setting: Single-centre prospective database study at a high-volume tertiary university hospital. Patients: 243 patients undergoing single-vessel stenting for de novo stenosis in 277 lesions. Exclusion criteria were bifurcational, graft or left main disease and intravascular imaging use. All had ischaemia-driven repeat coronary angiography up to 48 months later. Degree of stent overexpansion was the difference between nominal and final stent size. Results: Stents were expanded above nominal in 99% of cases and above rated burst pressure in 52%. Stents were expanded >20% above nominal in 12% of cases. Stents overexpanded by >20% were smaller (2.87 vs 3.19 mm), longer (24 vs 19 mm) and more often drug-eluting (53% vs 27%). Angiographic restenosis was observed in 80 lesions (29%). There was no correlation between degree of overexpansion and per cent angiographic restenosis across the whole group (R 2 =−0.01; p=0.09), in those with stent overexpansion >20% (p=0.31) or small stents <3 mm (p=0.71). Indeed, in the group with stent overexpansion >25%, the greater the overexpansion, the less the per cent angiographic restenosis (p=0.02). Conclusions: In this real-world population undergoing non-complex percutaneous coronary intervention without intravascular imaging, any tendency to overaggressive stent expansion did not predispose at all to restenosis.